Temozolomide down-regulates P-glycoprotein in human blood-brain barrier cells by disrupting Wnt3 signaling (2014)
Low delivery of many anticancer drugs across the blood-brain barrier (BBB) is a limitation to the success of chemotherapy in glioblastoma. This is because of the high levels of ATP-binding cassette transporters like P-glycoprotein (Pgp/ABCB1), which effluxes drugs back to the bloodstream. Temozolomide is one of the few agents able to cross the BBB; its effects on BBB cells permeability and Pgp activity are not known. We found that temozolomide, at therapeutic concentration, increased the transport of Pgp substrates across human brain microvascular endothelial cells and decreased the expression of Pgp. By methylating the promoter of Wnt3 gene, temozolomide lowers the endogenous synthesis of Wnt3 in BBB cells, disrupts the Wnt3/glycogen synthase kinase 3/?-catenin signaling, and reduces the binding of ?-catenin on the promoter of mdr1 gene, which encodes for Pgp. In co-culture models of BBB cells and human glioblastoma cells, pre-treatment with temozolomide increases the delivery, cytotoxicity, and antiproliferative effects of doxorubicin, vinblastine, and topotecan, three substrates of Pgp that are usually poorly delivered across BBB. Our work suggests that temozolomide increases the BBB permeability of drugs that are normally effluxed by Pgp back to the bloodstream. These findings may pave the way to new combinatorial chemotherapy schemes in glioblastoma. © 2013 Springer Basel.